2007
DOI: 10.1063/1.2733626
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of pentacene thin-film transistors and inverters with cross-linked poly(4-vinylphenol) gate dielectrics

Abstract: The authors report the effects of hydroxyl groups (OH bonds) on the electrical reliabilities of pentacene organic thin-film transistors (OTFTs) with poly-4-vinylphenol (PVP) gate dielectrics. PVP gate dielectric films mixed with different concentrations of methylated poly(melamine-co-formaldehyde) (MMF) were fabricated, and experiments on the hysteresis behavior of the OTFT device were conducted. Pentacene TFTs with the PVP (MMF 0wt.%) exhibited a large hysteresis, while in the PVP (MMF 125wt.%), nearly no hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(74 citation statements)
references
References 14 publications
1
71
1
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Gu et al 15,16 found that in the case of pentacene-based OFETs containing octadecyltrichlorosilanemodified SiO 2 gate dielectrics, the hysteresis observed during the full swing of a gate is due to long-lived charge traps present at the interface between semiconductor and gate dielectric, where trapping and detrapping of holes and electrons take place under an applied gate bias. [15][16][17][18] Further, water molecules in the air could create hysteresis-causing charge traps at the semiconductor/dielectric interface.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Gu et al 15,16 found that in the case of pentacene-based OFETs containing octadecyltrichlorosilanemodified SiO 2 gate dielectrics, the hysteresis observed during the full swing of a gate is due to long-lived charge traps present at the interface between semiconductor and gate dielectric, where trapping and detrapping of holes and electrons take place under an applied gate bias. [15][16][17][18] Further, water molecules in the air could create hysteresis-causing charge traps at the semiconductor/dielectric interface.…”
Section: Introductionmentioning
confidence: 97%
“…Although these results indicate that the formation of hysteresis-causing traps at the semiconductor/gate dielectric interface is strongly responsible for the observed hysteresis, the presence ͑in the dielectric bulk͒ of chemical species that cause slow polarization ͑e.g., polar functionalities, ionic impurities, and diffused water molecules͒ is also an important cause for the hysteresis observed in the OFETs. [23][24][25][26][27][28][29][30] When a polymer is used as the gate dielectric in an OFET, the end functionalities present both at the polymer surface and in the bulk have an important influence on the device performance ͑e.g., drain current, mobility, threshold voltage, and hysteresis͒. 7,31-33 Although polar functionalities, such as hydroxyl groups, are known to seriously affect the hysteresis observed during the operation of polymer-dielectric-based OFETs, 17,18,[22][23][24][25]28,29 there are only a few research papers that discuss in detail how each constituent of the polymer gate dielectric contributes to the origin and mechanism of the hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…PVP layer with cross-linking agent helps to reduce leakage current subsequently on/off ratio of the OFETs [20]. The cPVP as the dielectric of the OFETs may provide more stable device characteristics.…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…The hysteresis is mainly attributed to the dipoles which are present in the gate dielectric, and to the interaction with the ambient. A partial cross-linked process, which increases the effect of the hydroxyl groups in the gate dielectric layer, gives rise to these dipoles [67,68]. Conjointly, molecular oxygen and adsorbed water at the nanoparticle surface may induce variation in the film carrier concentration [69,70].…”
Section: Inorganic-based Tftmentioning
confidence: 99%